Three Aspects of the Linguistic Communion (Koinōnia) in Plato’s Sophist: Articulation of Letters, Predication of Names and Accord (Homologia) of Logoi - Karagöz, Taha (2022)
In the Sophist, Plato presents the possibility of the separation of things in relation to each other based on the communion (koinōnia) of logos. In this study, I discuss the linguistic communion revealed in the dialogue by illuminating its three fundamental aspects: (1) Articulation of letters in names as communion on the syntactic level, (2) Predication of names in logoi as communion on the semantic level, (3) Homologoi of logoi as the ultimate communion of language. I thus conclude that these three linguistic aspects are interdependent.